RESEARCH OF GAS DYNAMICS IN INTERCONTACT SPACE OF FRICTION SURFACES - Криштопа, Людмила Іванівна (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
For the design of physical and chemical and mathematical model of mechanism of migration of environment it is considered on the friction contact: adsorption, pumping over, crack effects and process of curriculum of phenol formaldehyde material under action of air and without its access.